Global Insights into Cultured Meat: Uncovering Production Processes, Potential Hazards, Regulatory Frameworks, and Key Challenges—A Scoping Review - Renata Puppin Zandonadi; Maíra Catharina Ramos; Flavia Tavares Silva Elias; Nathalia Sernizon Guimarães (Foods)
This scoping review aims to understand the cell-based meat production process, including the regulations, potential hazards, and critical points of this production. This review includes studies on cultured meat production processes, health hazards, and regulatory guidelines, excluding those without hazard analysis, incomplete texts, or studies published before 2013. The search was performed in eight electronic databases (MEDLINE, Web of Science, Embase, Cochrane Library, Scopus, LILACS, and Google Scholar) using MeSH terms and adaptations for each database. The search for local studies on regulations and guideline documents was complemented by a manual search on the websites of governments and regulatory agencies from different regions (e.g., FDA, FAO, EFSA, USDA, Health Canada, EC, EU, ANVISA/Brazil, MAPA/Brazil, FSANZ, and SFA). This step involved reading full texts to confirm eligibility and extract key data, including author, year, country, study design, objectives, results, cultured meat protocols, health hazards, and hazard control measures, followed by data analysis. A comprehensive search of the databases yielded 1185 studies and 46 regulatory or guidance documents. After removing duplicate studies and applying eligibility criteria to titles, abstracts and full texts, 35 studies and 45 regulatory or guidance documents were included. The cultured meat production protocols are well-established, highlighting potential hazards and critical control points. Although guidance documents and regulations are limited, they are expanding globally. The development and commercialization of cultured meat require clear, and up-to-date regulations and supervision, which are being studied and formulated by regulatory agencies worldwide. Cultured meat production presents some potential hazards (chemical, biological, and physical) that require food safety considerations: (i) genetic stability of cells/cell lines; (ii) microbiological hazards related to cell lines; (iii) exposure to substances used in the production process; (iv) toxicity and allergenicity of the product or its component for the population; (v) post-harvest microbiological contamination; (vi) chemical contamination/residue levels; and (vii) nutritional aspects/risks. Currently, no standardized testing approach exists for cultured meat. However, effective hazard and safety assessment strategies, such as HACCP combined with best practices, should be implemented throughout the production process.